Legalbewährung nach Entlassung aus dem offenen Vollzug Eine Vergleichsstudie - Schüttler, Helena (Edition Seehaus [plus] - Resozialisierung - Opferschutz - Restorative Justice, 2023)
Until now, there has been a lack of research on the effect of being incarcerated in an open prison on legal probation. Previous studies have mostly compared quite different groups of prisoners. In order to counteract this selection bias, this study forms comparable groups of prisoners from the open and closed prison systems using matching procedures. Data from the Federal Central Criminal Register were used to examine the rates, speed and severity of recidivism, while individual risk and protection factors were statistically checked. The results show that incarceration in an open prison has an independent effect on legal probation-beyond the effect of positive selection of prisoners-and significantly reduces reincarceration.